Efektivitas Pembelajaran Game-Based Learning melalui Permainan Bonakor terhadap Keterampilan Motorik Kasar Siswa Sekolah Dasar - Azfa Abdurrahman Yuri; Wulandari Putri; Eva Sri Gumilang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aim to determine the effect of implementing a Game-Based Learning approach through the colored tail ball game (Bonakor) on elementary school students’ gross motor skills. This research used a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest design. The sample consisted of 30 second-grade students of SDN 032 Tilil selected using purposive sampling. The research instrument used the Test of Gross Motor Development-Second Edition (TGMD-2). The results showed an increase in the mean TGMD-2 score from 85.8 in the pretest to 97.1 in the posttest, with a difference of 11.3 points. The Paired Samples t-test results indicated a significance value of < 0.001, meaning there was a significant difference between the pretest and posttest results. Therefore, the implementation of Game-Based Learning through the Bonakor game significantly improved students’ gross motor skills. The conclusion of this study indicates that a game-based learning approach is effective in improving elementary school students’ gross motor skills. The Bonakor game can be recommended as an alternative instructional media in physical education.   Keywords: Bonakor, Elementary School, Game-Based Learning, Gross Motor Skills, Physical Education.